Hubungan Gaya Kepemimpinan Kepala Ruangan Berdasarkan Persepsi Perawat Pelaksana Dengan Kinerja Perawat Di Rumah Sakit Murni Teguh Sudirman Jakarta - Saragih, Helidawaty; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2024)
Low quality of nurse performance will affect the image of the hospital or health care institution where the nurse works). The success of an organization in a hospital from several factors with one of them being human resources including a nurse, besides that the leader is also a factor that greatly influences the activities of his subordinates to do a job with a targeted achievement. Nurse performance can be influenced by several factors, including leadership style, motivation and work discipline. The purpose of this study was to determine the relationship between the leadership style of the head of the room based on the perception of the implementing nurse with the performance of nurses at Murni Teguh Sudirman Hospital, Jakarta. The research design used was correlative with a cross-sectional approach to determine the relationship between leadership style and nurse performance. The number of respondents was 68 people. Bivariate data analysis using the chi-square test. The results of the study showed that 34 respondents chose a democratic leadership style and 24 respondents chose an authoritarian leadership style. It was also found that 38 respondents had good performance, and 20 respondents had sufficient performance. There is a relationship between leadership style and nurse performance with a p-value = 0.023. It can be concluded that there is a significant relationship between the leadership style of the head of the room and the performance of nurses.